2020
DOI: 10.1074/jbc.ra119.011983
|View full text |Cite
|
Sign up to set email alerts
|

Protein secondary structure determines the temporal relationship between folding and disulfide formation

Abstract: How and when disulfide bonds form in proteins relative to the stage of their folding is a fundamental question in cell biology. Two models describe this relationship: the folded precursor model, in which a nascent structure forms before disulfides do, and the quasi-stochastic model, where disulfides form prior to folding. Here we investigated oxidative folding of three structurally diverse substrates, β2-microglobulin, prolactin, and the disintegrin domain of ADAM metallopeptidase domain 10 (ADAM10), to unders… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
2
21
1
1
Order By: Relevance
“…4C, lanes 3 and 5). We have previously shown that the disulfide-bonded products formed form this ADAM10 construct are present in nascent chains translocated into the ER lumen (Robinson, 2019). Taken together these results show that a source of non-membrane permeable reducing agent can resolve the non-native disulfides formed in nascent chains within the ER lumen.…”
Section: The Thioredoxin Reduction Pathway Is Sufficient To Reduce Nosupporting
confidence: 55%
See 3 more Smart Citations
“…4C, lanes 3 and 5). We have previously shown that the disulfide-bonded products formed form this ADAM10 construct are present in nascent chains translocated into the ER lumen (Robinson, 2019). Taken together these results show that a source of non-membrane permeable reducing agent can resolve the non-native disulfides formed in nascent chains within the ER lumen.…”
Section: The Thioredoxin Reduction Pathway Is Sufficient To Reduce Nosupporting
confidence: 55%
“…We previously demonstrated that non-native disulfides formed during the synthesis of β1-integrin require a cytosolic reductive pathway to ensure their isomerisation to the correct disulfides (Poet et al, 2017). To evaluate the ability of our reconstituted pathway to isomerise non-native disulfides, we generated stalled translocation intermediates of a protein that forms non-native disulfides following in vitro translation in the presence of semi-permeabilised (SP) cells (Robinson, 2019). By isolating SP-cells containing these intermediates we were then able to follow the rearrangement of disulfides post-translationally in the presence or absence of a TrxR1 reduction system (Fig.…”
Section: The Thioredoxin Reduction Pathway Is Sufficient To Reduce Nomentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that non-native disulfides formed during the synthesis of β1-integrin require a cytosolic reductive pathway to ensure their isomerisation to the correct disulfides (Poet et al, 2017). To evaluate the ability of our reconstituted pathway to isomerise non-native disulfides, we generated stalled translocation intermediates of a protein that forms non-native disulfides following in vitro translation in the presence of semi-permeabilised (SP) cells (Robinson, Kanemura et al, 2020).…”
Section: The Thioredoxin Reduction Pathway Is Sufficient To Reduce Nomentioning
confidence: 99%